Faktor - Faktor Yang Mempengaruhi Kunjungan ANC Pada Ibu Hamil di Puskesmas Pargarutan Tapanuli Selatan Tahun 2023 - Siti Maryam; Erin Padilla Siregar (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2023)
Antenatal care visits are influenced by two main factors. Based on the theory of Lawrence Green (1980), namely behavioral factors (behavioral causes) and factors outside of behavior (non-behavioral causes). Furthermore, the behavior itself is determined or formed from three factors, namely predisposing factors including age, level of education, parity of pregnant women, employment status, knowledge of pregnant women and attitudes of pregnant women. Enabling factors include family income, distance from residence and information media. Reinforcing factors include husband/family support. The aim of this research is to determine the factors that influence ANC visits at the South Tapanuli Pargarutan Community Health Center in 2023. This research method is analytical with a cross sectional approach with quantitative methods. The results of the research conducted showed that the number of respondents who had a negative attitude was 42 people and 31 people ( 73.8%) did not regularly make ANC visits, while 18 respondents who were positive and 14 people (77.8%) had regular antenatal visits. The RP value obtained was 3.32 (95%CI=1.37 - 8.03) indicating that mothers who had a negative attitude were 3.32 times more likely to have irregular ANC visits. People who have the principle of always living a healthy life will do anything for their health, especially for the fetus and pregnant mother. part of their family and life, one of which is by making good ANC visits